Analysis of Infections and All‐Cause Mortality in Phase II, Phase III, and Long‐Term Extension Studies of Tofacitinib in Patients With Rheumatoid Arthritis1. Issue 11 (November 2014) - Cohen, Stanley; Radominski, Sebastião C.; Gomez‐Reino, Juan J.; Wang, Lisy; Krishnaswami, Sriram; Wood, Susan P.; Soma, Koshika; Nduaka, Chudi I.; Kwok, Kenneth; Valdez, Hernan; Benda, Birgitta; Riese, Richard
<x xml:space="preserve">Abstract</x> Objective To determine the rate of infection and all‐cause mortality across tofacitinib phase II, phase III, and long‐term extension (LTE) studies in patients with moderately to severely active rheumatoid arthritis (RA). Methods Pooled data from studies of tofacitinib in patients with RA were analyzed. In these studies, tofacitinib was administered as monotherapy or in combination with methotrexate or other nonbiologic disease‐modifying antirheumatic drugs. The cutoff date for inclusion of data was April 19, 2012. Results Across phase II, phase III, and LTE studies, 4, 789 patients received tofacitinib (8, 460 patient‐years of exposure). The overall rate of serious infection was 3.09 events per 100 patient‐years (95% confidence interval [95% CI] 2.73–3.49), and rates were stable over time. A Cox proportional hazards model showed that age, corticosteroid dose, diabetes, and tofacitinib dose were independently linked to the risk of serious infection. Lymphocyte counts of <0.5 × 103/mm3 were rare but were associated with an increased risk of treated and/or serious infection. Overall, all‐cause mortality rates were 0.30 events per 100 patient‐years (95% CI 0.20–0.44). Conclusion The overall risk of infection (including serious infection) and mortality rates in RA patients treated with tofacitinib appear to be similar to those observed in RA patients treated with biologic agents. The rates of serious infection were stable over time.